NATIONAL FOOD SECURITY ACT: AREAS THAT NEED FOCUSED ATTENTION - Patel, Amrit (International Journal of Research -GRANTHAALAYAH, 2017)
The National Food Security Act [NFSA],2013 aims at covering overall 67% of population (75%of rural and 50%urban) and promising to give them rice/wheat/coarse cereals at Rs.3/2/1/Kg through Public Distribution System[PDS]. The quantity promised is 35kg/month for Antyodya households and 5kg/per person for priority households. At the current average size of the family of around 5, this will work to 25kg/household per month. The total annual requirement of food grains for beneficiaries of PDS and other welfare schemes is estimated to be 61.2 million tons [MT]. The cost of handling grain by the Government was about Rs.30/kg for rice and Rs.22/kg for wheat in 2014 (including costs of carrying stocks), against an Minimum Support Price [MSP] of rice at about Rs.20/kg (converted from paddy) and Rs.14/kg for wheat. The budgeted food subsidy for FY 2014-15 was Rs.1.15 billion and there were pending arrears of almost Rs.500 billion that need to be cleared on account of food subsidy. Against this background, this development perspective article highlights the current status of hunger in India, aspects of NFSA 2013, current agricultural scenario and specific areas that need focused attention.